IMPLEMENTASI PERATURAN MENTERI KOMUNIKASI DAN INFORMATIKA NOMOR 19 TAHUN 2014 DALAM PENANGANAN SITUS INTERNET BERMUATAN NEGATIF (Studi Kasus Pemblokiran terhadap Situs Radikal oleh Kemenkominfo Tahun 2015) - Najahan Musyafak; Maya Rini Handayani; Kumarudin . (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2017)
At the end of March 2015 the Ministry of Communications and Informatics (Kemenkominfo) blocking 22 internet sites that are considered radically charged or sympathizers of radicalism. Kemenkominfo serves to keep sites that campaignradicalism can be minimized. This authority is contained in the